Vazão ecológica no Espírito Santo sob a ótica dos direitos dos rios - Araujo, Alexandre Iunes Godinho (2023)
From the perspective of the Rights of Rivers, a subfield within the Rights of Nature paradigm, which offers a new approach to Environmental Law wherein the protection of Nature is justified intrinsically, this study offers a qualitative analysis of the methodologies and criteria employed by the State of Espírito Santo to determine grantable flows and, conversely, the minimum flow to which rivers and streams are entitled, referred to as ecological flow. Based on four pioneering cases of the recognition of rights to rivers, we initially identified the main initiatives, motivations, theoretical foundations, implementation formats, practical consequences, and challenges encountered in conferring rights to non-living natural entities, specifically in the cases of Vilcabamba (Ecuador), Atrato (Colombia), Ganges/Yamuna (India), and Whanganui (New Zealand). This study examines 14 (fourteen) processes for granting the right to use water resources within the State Water Resources Agency - SWRA, aiming to understand the methods, criteria, and priorities applied in the allocation of water use rights within the context of the emergent Right of Rivers framework. Guided by the set of methodological techniques called Content Analysis, this research scrutinizes the minimum residual flow defined in Sections of Reduced Flow – SRF’s of Hydroelectric Generation Plants – HGP’s through various comparative elements: the water body, watershed, and municipality; references to the term ecological flow; the reference flow mandated and prevailing environmental standards at the time of the granting ordinance; maximum grantable flow, minimum residual flow in the SRF, and applicable environmental standards during the issuance of the granting ordinance; minimum residual flow requested by the grantee for the SRF; minimum residual flow stipulated in the granting ordinance; conditions for validity in the granting ordinance; duration of grant orders; and statements from the licensing environmental body regarding ecological flow. Ultimately, the findings indicate a persisting gap in the comprehension of ecological flow issues, with atypical requirements and decisions that do not conflict with the Rights of Rivers. Conversely, has progressively incorporated environmental flow considerations in its recent decisions, demonstrating an increased sensitivity to ecosystemic factors when deliberating grantable flows, approached on a case-by-case basis within a holistic framework